SOME COMMON MISCONCEPTIONS RELATING TO ACCOUNTING EDUCATION. - Moye, C. A. (The Accounting Review, 1957)
Abstract This article discusses about some common misconceptions relating to accounting education. There has been a considerable amount of discussion during the past several years concerning accounting education. Some notions advanced have been based on misinformation or misunderstanding. Others have resulted from a lack of knowledge of some of the factors present. Some of the misconceptions are concerned with the general nature of accounting education, some consider suggested objectives or specific proposals, and some relate to the teaching of accounting. Probably the most common misconception today is that the study of accounting should blindly follow the same pattern as the study of some other professional field such as law or medicine. A second popular misconception, is the notion that accounting majors have had practically no courses other than accounting. A third area of confusion, is that employers are anxious to have accounting majors that complete a five or six year program before seeking employment. Many so-called problems are being posed today which many pessimistically portray as insurmountable. If the experiences of the past are indicative, it can be expected that changes which evolve, will represent continued progress and that accounting education will keep pace with the increasing responsibilities assigned to it.